Machine Hearts and Wandering Spirits in Nietzsche and Zhuangzi - Froese, Katrin (Religions, 2018)
Both Nietzsche and Zhuangzi spurn the boundaries of human convention and traditional authority and maintain that the ego-self, based on the internalization of external norms is its unwelcome byproduct. In an attempt to counteract this, these thinkers espouse a wandering approach to existence, which would affirm the existence of the variegated and perpetually evolving cosmos and help to undo the often pernicious effects of the objectification of language. Paradoxically, they maintain that a deep connection to other beings and the natural world necessitates a willingness to embrace solitude and also the dissolution of the self.